Dietary and Physical Activity Practices and Preferences in Children: An Approach from School Parliaments in Educational Public Establishments [Prácticas y Preferencias Alimentarias y de Actividad Física en Niños y Niñas: Una Aproximación Desde Los Parlamentos Escolares en Establecimientos Educacionales] - Palacios-Pino, J; Margarit-Segura, D; Gonzalez-Catalan, D; Pizarro-Quevedo, T; Suarez-Reyes, M (Sociedad Chilena de Pediatria, 2023)
In Chile, overnutrition continues to increase, especially affecting children. Solving this public health problem requires the development of promotion and prevention strategies that consider the suggestions of the communities, especially those of the children themselves. Objective: To know the opinions and suggestions of third and fourth-grade children from schools in the southern area of San-tiago, Chile, regarding their eating practices and physical activity, as part of the FONDEF IT 1810016 project. Subjects and Method: Seven School Meetings were held in seven schools using a participatory qualitative methodology, collecting the opinions of 176 children regarding both their food and physical activity habits and preferences. Results: The most consumed and preferred foods are those easy to prepare and highly available, such as bread, pasta, and milk. Foods that require preparation or are less available, such as fish, legumes, fruits, vegetables, and homemade preparations, are less consumed and have less preference. Regarding physical activities, video games and soccer stand out. Students propose increasing the hours of physical education and recesses and improving the availability and access to healthy foods in school environments as a solution strategy. Conclusions: School Meetings as a participatory strategy contribute to the joint generation of knowledge. The need to include communities as participants in health initiatives recognizes, through their role, children as subjects of rights. © 2023, Sociedad Chilena de Pediatria. All rights reserved.